Cover Picture: Sterically Demanding Unsymmetrical Diaryl‐λ3‐iodanes for Electrophilic Pentafluorophenylation and an Approach to α‐Pentafluorophenyl Carbonyl Compounds with an All‐Carbon Stereocenter (ChemistryOpen 6/2014). Issue 6 (December 2014) - Matsuzaki, Kohei; Okuyama, Kenta; Tokunaga, Etsuko; Shiro, Motoo; Shibata, Norio
<x xml:space="preserve">Abstract</x> The cover picture shows the Japanese painting "Genshi‐Chi" ("Primitive Land") by Mami Shibata: our state‐of‐the‐art reagent for pentafluorophenylation is realized by the cooperation of the halogens fluorine and iodine—elements from the primitive Earth. In the study, sterically demanding unsymmetrical pentafluorophenyl‐triisopropylphenyl‐λ3‐iodane was developed as an effective reagent for the electrophilic pentafluorophenylation of various β‐keto esters and a β‐keto amide. 17 examples of α‐pentafluorophenylated 1, 3‐dicarbonyl compounds with quaternary carbon centers are provided. For more details, see the Communication by Norio Shibata on 10.1002/open.201402045 ((p. 233 ff.))<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>